(untitled) (Marketing Journal, 2025)
This article is devoted to the issues of increasing the efficiency of capital use in enterprises, and analyzes the role and importance of investment resources in ensuring the sustainable development of the national economy. The study examines methods for assessing the efficiency of capital investments, existing problems in enterprises and ways to eliminate them. The article systematically analyzes the factors affecting the efficiency of capital use and develops practical proposals and recommendations based on innovative, organizational and financial mechanisms aimed at increasing efficiency. 136 The author offers specific recommendations and practical mechanisms for increasing efficiency.